2022
DOI: 10.3389/fmicb.2022.1014910
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of tetracycline resistance genes and microbiomes from manure-borne black soldier fly larvae frass to rhizosphere soil and pakchoi endophytes

Abstract: Manure treatment with black soldier fly larvae (BSFL) and BSFL frass application in crop land is a sustainable strategy; however, whether residual antibiotic resistance genes (ARGs) and their transmission risk are related to the manure BSFL treatment process is still unknown. In this paper, the effect of BSFL addition density on residual tetracycline resistance genes (TRGs) and transmission from frass to pakchoi was determined. The results showed that BSFL frass can provide sufficient nutrients for growth, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The rhizosphere is a sensitive soil area that is susceptible to exogenous chemicals, where roots interact with physical, chemical, and biological soil properties [ 24 ]. Several studies have shown that manure application substantially increases the antibiotic resistance profiles of microbial communities in the rhizosphere, root endophytes and phyllosphere of crops, such as corn, wheat, rice, and vegetables [ 25 , 26 , 27 ]. However, microbiomes with antibiotic resistance profiles are determined by a combination of indigenous microbes and antibiotic residuals, and are regulated by a variety of environmental factors [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rhizosphere is a sensitive soil area that is susceptible to exogenous chemicals, where roots interact with physical, chemical, and biological soil properties [ 24 ]. Several studies have shown that manure application substantially increases the antibiotic resistance profiles of microbial communities in the rhizosphere, root endophytes and phyllosphere of crops, such as corn, wheat, rice, and vegetables [ 25 , 26 , 27 ]. However, microbiomes with antibiotic resistance profiles are determined by a combination of indigenous microbes and antibiotic residuals, and are regulated by a variety of environmental factors [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%